Edukasi Manajemen Keuangan Pribadi untuk Meningkatkan Literasi Finansial Siswa SMK Handayani Manggar, Belitung Timur - Siti Ruhana Dara; Vina Meliana (LPMP Imperium, 2026)
According to the Financial Services Authority (OJK), financial literacy constitutes the knowledge, skills, and confidence that influence attitudes and behaviors in decision-making and financial management to achieve financial well-being. This understanding is crucial from an early age, particularly for Generation Z, who are growing up in a digital era and facing increasingly complex financial dynamics. This Community Service (PKM) activity, conducted by lecturers from Kalbis University at SMK Handayani Manggar, East Belitung, aims to enhance students' financial literacy through direct education on personal financial management. The activity was held on December 12, 2024, using a participatory approach that covered personal financial management, the distinction between needs and wants, savings and investment, and financial management strategies tailored for Generation Z. The indicators of success for this activity were evident from the high level of enthusiasm and active participation of 85 students in discussion sessions, improved understanding shown by the students' ability to identify spending priorities, and a strong desire to implement independent personal financial recording post-activity.